2022
DOI: 10.1093/cid/ciac511
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic-Pharmacodynamic Determinants of Clinical Outcomes for Rifampin-Resistant Tuberculosis: A Multisite Prospective Cohort Study

Abstract: Background Treatment of rifampin-resistant and/or multidrug-resistant tuberculosis (RR/MDR-TB) requires multiple drugs and outcomes remain suboptimal. Some drugs are associated with improved outcome, however whether particular pharmacokinetic-pharmacodynamic relationships predict outcome is unknown. Methods Adults with pulmonary RR/MDR-TB in Tanzania, Bangladesh and Russian Federation receiving therapy with local regimens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In 105 patients with MDR-TB receiving clofazimine, an AUC/MIC ratio of >50 was associated with faster time to sputum culture conversion. 10 A similar correlation between higher AUC/MIC ratios and 2 and 6 month culture conversion was recorded in 136 MDR-TB patients receiving clofazimine. 38 A similar signal was observed in NTM disease.…”
Section: Perspectivementioning
confidence: 56%
See 1 more Smart Citation
“…In 105 patients with MDR-TB receiving clofazimine, an AUC/MIC ratio of >50 was associated with faster time to sputum culture conversion. 10 A similar correlation between higher AUC/MIC ratios and 2 and 6 month culture conversion was recorded in 136 MDR-TB patients receiving clofazimine. 38 A similar signal was observed in NTM disease.…”
Section: Perspectivementioning
confidence: 56%
“… 7 Achieving adequate exposures fast seems important, as clofazimine shows exposure-driven sterilizing and a treatment-shortening effect in TB in mouse models 8 , 9 and in patients with MDR-TB. 10 …”
Section: Introductionmentioning
confidence: 99%
“…These symptoms are consistent with findings from multiple studies. 15,16 However, a study in Nigeria reported that knowledge about TB was a significant factor affecting treatment adherence and outcomes, implying that clinical presentations alone may not be sufficient indicators of treatment success. 17 In terms of treatment duration, most participants had a TB presentation lasting more than one month (61.38%).…”
Section: Discussionmentioning
confidence: 99%